Analisis Penerapan Activity Based Costing (ABC) dalam Penentuan Harga Pokok Produksi Guna Mengurangi Distorsi Biaya pada Perusahaan Manufaktur - Debby Anastasya Panggabean; Yessi Annta Gultom; Hansen Alan Silalahi; E. Hamonangan Siallagan (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of the industrial world demands accuracy in determining the Cost of Goods Manufactured (COGM) to avoid cost distortion. Many manufacturing companies still implement traditional volume-based methods with a single driver, which triggers undercosting and overcosting. This study aims to analyze the implementation of the Activity-Based Costing (ABC) method in determining COGM to mitigate cost distortion. The research method used is descriptive qualitative by identifying production activities, grouping them into cost pools, determining cost drivers, and comparing the results with traditional methods. The results show that overhead activities are classified into five main components: purchasing cost, storage cost, machine cost, packaging cost, and distribution cost. Based on data calculation, the traditional method generates significant cost distortion, where Product A experiences undercosting of Rp800,000 and Product B experiences overcosting of Rp800,000. Conversely, the implementation of the ABC method utilizing multiple cost drivers is proven to allocate overhead costs proportionally according to actual activity consumption. The implication is that the ABC method provides higher quality and more accurate cost information to support operational efficiency, strategic pricing, and management profit planning.